L’uso delle basi di dati elettroniche nello studio della ricezione letteraria - Tedeschi, Stefano (Status Quaestionis, 2017)
The essay wants to answer the question of measuring the reception of a foreign literature through the use of data set of translations published in a given period. The tools provided by the Sociology of Literature and the Reception Studies can be connected with databases to achieve important results, especially when the publishing strategies of the translations respond to defined logic within the defined cultural field, as occurs in Italy with the Spanish-American Literature in the second half of the Twentieth Century.